A Hospital-Based, Single-Center, Cross-Sectional Study to Investigate the Status Quo of Hyperuricaemia in a Booming Seaside City with Young Population from 2020 to 2021 in China - Li C; Sun J; Wei Q; Yue J; Wang X; Zhang Q; Peng S; Liao X; Zeng H; Asakawa T (International Journal of General Medicine)
Chunyan Li,1,* Jiajia Sun,1,2,* Qifeng Wei,3,* Jianrong Yue,1 Xuefei Wang,1 Qin Zhang,1 Shiping Peng,1 Xiujuan Liao,1 Hui Zeng,4 Tetsuya Asakawa5 1Department of Health Management, National Clinical Research Center for Infectious Diseases, Shenzhen Third People’s Hospital, Shenzhen, Guangdong Province, People’s Republic of China; 2Faculty of Medicine, Macau University of Science and Technology, Macao, People’s Republic of China; 3Department of Orthopedics, National Clinical Research Center for Infectious Diseases, Shenzhen Third People’s Hospital, Shenzhen, Guangdong Province, People’s Republic of China; 4Department of Health Services Section, National Clinical Research Center for Infectious Diseases, Shenzhen Third People’s Hospital, Shenzhen, Guangdong Province, People’s Republic of China; 5Institute of Neurology, National Clinical Research Center for Infectious Diseases, Shenzhen Third People’s Hospital, Shenzhen, Guangdong Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tetsuya Asakawa, Institute of Neurology, National Clinical Research Center for Infectious Diseases, Shenzhen Third People’s Hospital, 29 Bulan Road, Shenzhen, Guangdong Province, 518112, People’s Republic of China, Email asakawat1971@gmail.com Hui Zeng, Department of Health Services Section, National Clinical Research Center for Infectious Diseases, Shenzhen Third People’s Hospital, 29 Bulan Road, Shenzhen, Guangdong Province, 518112, People’s Republic of China, Email 24178743@qq.comBackground: This is a hospital-based, single-center, cross-sectional study to investigate the status quo of hyperuricaemia (HUA) in general adults in Shenzhen, a booming seaside city in the South China.Methods: All health adults (≥ 18 years old) undergoing health examination from 2020 Oct 1 to 2021 September 30 in a general hospital were enrolled. Their medical records were investigated and analyzed.Results: Total 4604 participants (2938 males and 1756 females) were included and analyzed. We found that although the participants in Shenzhen were younger than the people included the analogous study in the adjacent cities (total 38.41 ± 10.33 years, 39.11 ± 10.18 in males and 37.24 ± 10.47 in females), the prevalence of HUA reached to amazing 34.7% (43.5% in males and 20.1% in females). Moreover, great HUA-related gender difference was found in terms of age-related variation trends of HUA prevalence (P < 0.001), indices of laboratory examination (P < 0.01) and influence factors (P < 0.001).Conclusion: These results raise alarm bells for the HUA problem in the booming seaside city with young population like Shenzhen in China (2020– 2021). Effective measures are appealed to reduce the high prevalence of HUA of Shenzhen. In addition, during analyses of the data, we found that both the prevalence of HUA and age of the population need to be seriously considered. Accordingly, we propose a more representative index, namely “Prevalence-Age Index (PAI = Prevalence of HUA/Average age)” to be used in the future HUA-related investigations.Keywords: hyperuricaemia, prevalence, gender difference, risk factors, protective factors